Nutritional Assessment and Sensory Properties of Dried Pap Fortified with Soybean and Date Palm Fruit Flours (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
The nutritional inadequacy of exclusive breastfeeding becomes evident from six months onwards, highlighting the importance of introducing complementary foods to ensure optimal infant nutrition. This study evaluated the nutritional and sensory properties of dried pap fortified with soybean and date palm flours using face central Design. Maize grain was cleaned, washed, soaked in potable water for 72h, wet millet, sieved, dried in a cabinet dryer for 8h at 50 oC; the date palm fruit was washed deseeded, dehydrated at 50 oC for 30 min, ground and sieved with 1.19mm mesh. Soybean seed was washed soaked for 12h at 30 oC, dehulled, boiled for 2h at 80 oC, dried at 60 oC for 24h, milled and sieved using 600 µm mesh size. The moisture, ash, fat, protein, fibre and carbohydrate contents ranged from 6.20 – 7.06 %, 3.25 – 5.10%, 4.37 – 14.67%, 7.72 – 16.87 %, 12.49 – 21.97% and 35.22 – 65.48 %, respectively. Bulk density, swelling capacity and water absorption capacity ranged significantly from 0.07 – 0.79 g/c3, 0.845 – 1.060 g/g and 0.898 – 0.955 g/g respectively. The sensory attributes of the pap samples varied significantly in terms of colour, odour, flavor and overall acceptability. It was 5 g date flour plus 5 g soybean flour was the most preferred besides the control samples. The finding of this study suggest that dried pap fortified with soybean and date palm flours has the potential to improve the nutrients and sensory quality of the product.